Clinical Presentation and Determinants of Mortality of Invasive Pulmonary Aspergillosis in Kidney Transplant Recipients: A Multinational Cohort Study. Issue 11 (31st May 2016) - López‐Medrano, F.; Fernández‐Ruiz, M.; Silva, J. T.; Carver, P. L.; van Delden, C.; Merino, E.; Pérez‐Saez, M. J.; Montero, M.; Coussement, J.; de Abreu Mazzolin, M.; Cervera, C.; Santos, L.; et al.
Abstract : The prognostic factors and optimal therapy for invasive pulmonary aspergillosis (IPA) after kidney transplantation (KT) remain poorly studied. We included in this multinational retrospective study 112 recipients diagnosed with probable (75.0% of cases) or proven (25.0%) IPA between 2000 and 2013. The median interval from transplantation to diagnosis was 230 days. Cough, fever, and expectoration were the most common symptoms at presentation. Bilateral pulmonary involvement was observed in 63.6% of cases. Positivity rates for the galactomannan assay in serum and bronchoalveolar lavage samples were 61.3% and 57.1%, respectively. Aspergillus fumigatus was the most commonly identified species. Six‐ and 12‐week survival rates were 68.8% and 60.7%, respectively, and 22.1% of survivors experienced graft loss. Occurrence of IPA within the first 6 months (hazard ratio [HR]: 2.29; p ‐ value = 0.027) and bilateral involvement at diagnosis (HR: 3.00; p ‐ value = 0.017) were independent predictors for 6‐week all‐cause mortality, whereas the initial use of a voriconazole‐based regimen showed a protective effect (HR: 0.34; p ‐ value = 0.007). The administration of antifungal combination therapy had no apparent impact on outcome. In conclusion, IPA entails a dismal prognosis among KT recipients. Maintaining a low clinical suspicion threshold is key to achieve a prompt diagnosis and to initiate voriconazole therapy. Abstract : Invasive pulmonary aspergillosis presents a high mortality rate in kidney transplant recipients, with diagnosis within the first 6 months posttransplantation and bilateral lung involvement as independent risk factors for mortality.